Minding the Stock : Bringing Public Policy to Bear on Livestock Sector Development - World Bank (World Bank, 2012)
Driven by population growth, urbanization, and increased income, the demand for animal-source food products in developing countries is rapidly increasing. Livestock, which already constitutes 30 percent of the agricultural Gross Domestic Product (GDP) in the developing world, and about 40 percent of the global agricultural GDP, is one of the fastest-growing subsectors in agriculture. Growing demand presents real opportunities for economic growth and poverty reduction in rural areas. It could directly benefit the one billion poor people who depend on livestock as a source of income and subsistence. Livestock also provides traction for about 50 percent of the world's farmers and is a source of organic fertilizer for most of the world's croplands, converting waste products into inputs in the production of high-value food. For these reasons, the sector has a critical role to play in making agriculture sustainable, in reducing poverty, and in contributing to economic growth. This report presents an analysis of the issues related to market failures in the livestock sector, and an examination of policy and investment options that can be used to overcome them. Its principal intended audience includes policy makers and development practitioners. Much of the analysis will focus on identifying the needs of the public sector as it sets out to redress the imbalance between public and private investment and to begin establishing an enabling environment in which private sector livestock development can take place in a way that is consistent with public health, poverty reduction, and environmental sustainability. While the report focuses on developing countries, much of its treatment pertains to industrialized countries as well, particularly with respect to issues of crosscutting global significance, such as greenhouse gas emissions and emerging highly infectious diseases.